Differential Expression of Motilin Receptor in Various Parts of Gastrointestinal Tract in Dogs - Yu He; Hui Wang; DongYan Yang; ChengYan Wang; LanLan Yang; Chunxiang Jin (Gastroenterology Research and Practice)
Objectives. The presence of motilin receptor in the GI tract of different animal species has been verified. However, the quantitation of motilin receptor expression in different regions of the GI tract remains unclear. The aim of this study was to investigate the expression of motilin receptor in the GI tract and semiquantitatively compare the expression difference in different GI regions in dogs. Methods. Antrum, duodenum, jejunum, ileum, proximal colon, middle colon, and distal colon were obtained from various parts of the GI tract of six sacrificed dogs. The distribution of motilin receptor was determined by immunohistochemistry. The expression levels of motilin receptor mRNA in different regions were measured by RT-PCR. Results. Motilin receptor was expressed throughout the GI tract in dogs. Multiple comparisons of the mean motilin receptor mRNA expression among various regions were significant (P<0.05). Motilin receptor mRNA was extensively expressed in duodenum, followed by ileum, jejunum, proximal colon, antrum, middle colon, and distal colon. Immunohistochemistry revealed that motilin receptor immunoreactivity was observed only in the enteric nervous system. Conclusion. Motilin receptor is expressed differentially along the GI tract in dogs. The significantly high expression of motilin receptor mRNA is found in the duodenum.